UPAYA MENINGKATKAN KEMAMPUAN MERANCANG PEMBELAJARAN MELALUI KEGIATAN WORKSHOP TERSTRUKTUR PADA GURU DI SD NEGERI GIRIPURNO 2 - Ali Masykuri (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2022)
The ability of a teacher as an educator in designing learning is a competency that must be possessed. Teachers have a crucial role in the process of scientific transition. However, there are still problems found that the process of preparing lesson plans as teaching materials is not by following with a systematic format, the applied learning methods have not been able to actively involve students, and there are still teachers who prepare lesson plans with copy and paste. The condition of teachers' lack of competence in designing learning materials is the reason for this research. The focus of this research is to make efforts to improve the ability of teachers in designing learning materials that are carried out through structured workshop activities, especially for teachers at SD Negeri Giripurno 2. The subject of this research is the competence of teachers at SD Negeri Giripurno 2 by collecting qualitative and descriptive comparative data. The results showed that efforts to improve the ability to design learning progressed through structured workshop activities for teachers at SD Negeri Giripurno 2.